2023
DOI: 10.1002/ajmg.a.63181
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and descriptive epidemiology of Turner syndrome in the United States, 2000–2017: A report from the National Birth Defects Prevention Network

Abstract: The lack of United States population‐based data on Turner syndrome limits assessments of prevalence and associated characteristics for this sex chromosome abnormality. Therefore, we collated 2000–2017 data from seven birth defects surveillance programs within the National Birth Defects Prevention Network. We estimated the prevalence of karyotype‐confirmed Turner syndrome diagnosed within the first year of life. We also calculated the proportion of cases with commonly ascertained birth defects, assessed associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This was calculated in days from birth until the death of an infant or until the infant was aged 1 year, with censoring at 1 year. Based on prior work (Benjamin et al, 2021(Benjamin et al, , 2023Marengo et al, 2014Marengo et al, , 2023Martin-Giacalone et al, 2023;Vendola et al, 2010), infants without death records were assumed to have survived to their first birthday. Several independent variables were considered, including maternal race and ethnicity (non-Hispanic White [White], non-Hispanic Black [Black], Hispanic, and additional groups), maternal age at delivery (<35 years or ≥ 35 years), maternal education at delivery (less than high school [<12 years] high school [12 years], and more than high school [>12 years]), preterm birth (gestational age < 37 weeks or ≥ 37 weeks at delivery), birthweight (<2500 grams or ≥ 2500 grams), clinical classification for infants with hydrocephaly (isolated, chromosomal or syndromic, and multiple), and birth year (1999-2011 or 2012-2017) (Supplement A).…”
Section: Outcome and Independent Variablesmentioning
confidence: 99%
“…This was calculated in days from birth until the death of an infant or until the infant was aged 1 year, with censoring at 1 year. Based on prior work (Benjamin et al, 2021(Benjamin et al, , 2023Marengo et al, 2014Marengo et al, , 2023Martin-Giacalone et al, 2023;Vendola et al, 2010), infants without death records were assumed to have survived to their first birthday. Several independent variables were considered, including maternal race and ethnicity (non-Hispanic White [White], non-Hispanic Black [Black], Hispanic, and additional groups), maternal age at delivery (<35 years or ≥ 35 years), maternal education at delivery (less than high school [<12 years] high school [12 years], and more than high school [>12 years]), preterm birth (gestational age < 37 weeks or ≥ 37 weeks at delivery), birthweight (<2500 grams or ≥ 2500 grams), clinical classification for infants with hydrocephaly (isolated, chromosomal or syndromic, and multiple), and birth year (1999-2011 or 2012-2017) (Supplement A).…”
Section: Outcome and Independent Variablesmentioning
confidence: 99%
“…Turner syndrome (TS) is a condition that results from a completely or partially missing X chromosome. This is the most common chromosomal anomaly in females, occurring in approximately one in 2000-3000 live female births [ 1 ]. Girls and women with TS typically present with short stature and ovarian dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, this has led to publications describing small cohorts at single institutions with ascertainment bias resulting in underpowered studies. One recent US population‐based study of the prevalence of karyotype‐confirmed diagnosis of TS in the first year of life, utilizing data from seven birth defects surveillance programs reflects the challenges in case ascertainment in the absence of nationalized health care registry data (Martin‐Giacalone et al, 2023). Larger scale data have been reported from such registries in European countries (Baena et al, 2004; Gravholt et al, 1998); however, neither the racial/ethnic composition nor socioeconomic structure in these countries accurately reflect the US population.…”
Section: Introductionmentioning
confidence: 99%